Generating a Metro Manila activity-based model applying structural equation modeling approach - Ejes, Claudine Marie Torres (2001)
This papergenerates, estimates, and interprets an activity-based model using structural equation modeling methodlogy applied to the 1996 data set from the Mtero Manila Urban Transportation Integration Study (MMUTIS). Structural Euation Modeling (SEM) and Activity-Based Analysis (ABA) are thoroughly discussed. Latent constructs are specified, possible relationships among them are hypothesized, and various diagrams and tables detailing these relationships are presented. The SEM-based software LISREL produced reasonable parameter estimates. Suggested fit indices indicate a good data-model-fit and apparent inconsistencies are significant. This study begot interpretable results and practical recommendations for future researchers.